Enhancement of Functional Properties of Cotton by Conventional Dyeing with Tio2 Nanoparticles. (2015) - Khandual, A.; Luximon, A.; Sachdeva, A.; Rout, N.; Sahoo, P.K.
Abstract: We investigated a simple way of incorporating TiO2 nano particle with reactive vinyl sulphone class dyeing of cotton. It has been observed that there is significant and lasting improvement in strength, wear resistance, stiffness and UV protection. The experimental results obtained from SEM, Raman, FTIR and UV visible spectral analysis along with physical property tests confirms the diffusion of TiO2 nanoparticle along with dye into the fibre polymer matrix.